Effects of intermittent hypoxic training performed at high hypoxia level on exercise performance in highly trained runners - Sanchez, A. M. J.; Borrani, F. (Journal of Sports Sciences, 2018)
This study exanimated the effects of intermittent hypoxic training (IHT) conducted at a high level of hypoxia with recovery at ambient air on aerobic/anaerobic capacities at sea level and hematological variations. According to a double-blind randomized design, fifteen highly endurance-trained runners completed a 6-weeks regimented training with 3 sessions per week consisting of intermittent runs (6x work-rest ratio of 5':5') on a treadmill at 80-85% of maximal aerobic speed (). Nine athletes (hypoxic group, HG) performed the exercise bouts at FI02 = 10.6-11.4% while six athletes (normoxic group, NG) exercised at ambient air. Running time to exhaustion at a velocity corresponding to 95% significantly increased for HG while no effect was found for NG. Regarding , no significant effects were found in either training group. In addition, the decline of jumping performances over a 45s-continuous maximal vertical jump test (i.e. anaerobic capacity index) tended to be lower in HG compared to NG. The levels of the studied hematological variables, including erythropoietin and hematocrit, did not significantly change for either HG or NG. These results highlight that our IHT protocol may induce additional effects on aerobic performance without compromising the anaerobic capacity index in highly-trained athletes.